Integration of Edupark and Digital Technology: Analysis of the Need for a Physics Learning Website to Address Misconceptions - Lathifa Khairani; Hamdi Rifai; Husna (Jurnal Penelitian Pendidikan IPA, 2025)
The integration of digital technology with a contextual learning approach is a strategic solution to improve conceptual understanding and reduce misconceptions in physics learning. This study aims to analyze the need for developing website-based learning media that integrates the concept of edupark as a contextual approach. The method used in this needs analysis employs the EDUPARK development model, limited to the EDU stage. Data collection instruments include the EDUPARK potential format, physics concept observation sheets at the EDUPARK, questionnaires, interview sheets, and curriculum reviews at SMAN 4 Padang. The results of the Edupark Finding stage identified the Lumindai Stone Forest tourist attraction. The Direct Observation stage revealed that the physics concepts present at the edupark location include gravity and equilibrium, thermodynamics, sound and light waves, and energy. Finally, the Understanding of Teacher, Students, and Curriculum Characteristics stage revealed that students experienced high levels of misconceptions due to the lack of interactive and contextual media, as well as the suboptimal utilization of local potential (edupark). To address these issues, the integrated edupark learning website is viewed as an innovative solution to support the Merdeka Curriculum and enhance the quality of physics education.